THE CLASSIFICATION AND MEANING OF FIGURATIVE LANGUAGE IN THE ENCANTO MOVIE - Miftakhul Bayty Jannah; Devi Rosmawati; Yohanes Angie Kristiawan (JOLALI: Journal of Language and Literature, 2023)
This research aims to determine the types and meanings expressed in figurative language in the Encanto movie. The data are the movie script. The research employs Kennedy, Verdonk and Perrine’s theory on figurative language, and Leech’s theory on meaning to identify the types and meanings of figurative language in the Encanto movie script. The results of this research indicate that there are 10 out of 13 types of figurative language from 71 data. The type of figurative language with the highest frequency is metaphor and paradox as much as 14 frequencies (19.71%). The second is personification as much as 12 frequencies (16.90%). Then irony as much as eight frequencies (11.26%), simile and idiom are seven frequencies (9.85%), repetition and onomatopoeia are three frequencies (4.22%), and litotes is two frequencies (2.81%). The lowest frequency is euphemism with only 1 frequency (1.40%). Meanwhile, the meaning expressed is divided into seven types. Connotative meaning is the highest type of meaning that appears, as much as 29 frequencies (40.84%). The second highest is affective meaning as much as 24 frequencies (33.80%). Then, conceptual meaning is 10 frequencies (14.08%), social meaning is four frequencies (5.63%), and collocative meaning is two frequencies (2.81%). The type of meaning with the lowest frequency is reflective and thematic meaning found only one frequency (1.40%).